Recognition of the nucleosome by the chromatin remodeler atrx - Feng, Xiaoyu (2017)
The α-thalassemia mental retardation X-linked protein (ATRX) is an ATP-dependent chromatin remodeler. Congenital mutations in ATRX cause a rare inherited disease called ATRX syndrome and somatic mutations in ATRX may involve in cancer development. There are two main domains in ATRX. One is the C-terminal helicase domain which has the ability to translocate along DNA coupled with ATP hydrolysis. The other one is the N-terminal ATRX-DNMT3-DNMT3L (ADD) domain which participates in ATRX recruitment to chromatin. Among the ATRX syndrome associated missense mutations, ~30% are located in the helicase domain and ~50% occur in the ADD domain. It is reported that the ADD domain recognizes the tri-methylated Lys9 and the unmodified Lys4 on the histone H3 tail peptide. But how the ADD domain functions in the nucleosomal context is still unknown. The results presented in this dissertation provide evidence that ATRX dimerizes both in vitro and in vivo through a coiled-coil motif (CC) localized downstream of the ADD domain. Furthermore, the ADD domain recognizes H3K9me3 mark in the nucleosomal context. The three-dimensional structure of the ADD-CC/NCP (H3.1K9me3) complex was obtained using cryo-EM. Fitting the known ADD domain and NCP structures into the EM map suggests that only one ADD monomer in the ADD-CC dimer contacts the NCP as well as nucleosomal DNA. Subsequent biochemical studies provide evidence that the ADD-CC dimer binds to di-nucleosomes with higher affinity than to mono-nucleosomes and the binding is insensitive to the length of the linker DNA between di-nucleosomes. The GATA-like zinc-finger on the ADD domain is the major DNA-binding motif.